2013
DOI: 10.4093/dmj.2013.37.6.458
|View full text |Cite
|
Sign up to set email alerts
|

Relative Skeletal Muscle Mass Is Associated with Development of Metabolic Syndrome

Abstract: BackgroundVisceral adiposity is related to insulin resistance. Skeletal muscle plays a central role in insulin-mediated glucose disposal; however, little is known about the association between muscle mass and metabolic syndrome (MS). This study is to clarify the clinical role of skeletal muscle mass in development of MS.MethodsA total of 1,042 subjects were enrolled. Subjects with prior MS and chronic diseases were excluded. After 24 months, development of MS was assessed using NCEP-ATP III criteria. Skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 21 publications
9
82
0
4
Order By: Relevance
“…The fat percent in muscle has been shown to be a determinant for metabolic disease, inflammation and non-chronic diseases [22]. Indeed, the present results confirm that there are strong correlations between fat percent and indices for desaturases and elongases, apparent supporting the role of muscle fat percent as a marker in relation to chronic diseases in man.…”
Section: Discussionsupporting
confidence: 84%
“…The fat percent in muscle has been shown to be a determinant for metabolic disease, inflammation and non-chronic diseases [22]. Indeed, the present results confirm that there are strong correlations between fat percent and indices for desaturases and elongases, apparent supporting the role of muscle fat percent as a marker in relation to chronic diseases in man.…”
Section: Discussionsupporting
confidence: 84%
“…This is a variation of a measure introduced recently [25]. To rank the subjects according to RMM we distributed them into quartiles.…”
Section: Methodsmentioning
confidence: 99%
“…utilization and secretion of myokines that mediate crosstalk among muscle, liver, adipose tissue, and other organs. (6,7) Several studies have reported that low muscle mass is associated with the prevalence of NAFLD in cross-sectional settings, (8)(9)(10)(11) but longitudinal data exploring the causal relationship between low muscle mass and NAFLD are limited. In addition, the effect of skeletal muscle mass on the resolution of existing NAFLD is poorly understood.…”
Section: Relationship Between Relative Skeletal Muscle Mass and Nonalmentioning
confidence: 99%